Antioxidant and Sunscreen Activity from Nanoparticles Extract of Temulawak Rhizome (Curcuma Xanthorrhiza Roxb.) And Formulation in The Form of A Cream - Anarisa Budiati; Deni Rahmat; Zahirah Alwiyah (Jurnal Jamu Indonesia, 2021)
Temulawak (Curcuma xanthorrhiza Roxb.) is a medicinal plant for the raw material of traditional medicine in Indonesia. Temulawak can be a source of antioxidants and natural sunscreen because of its curcumin content. This study was conducted to determine antioxidant and sunscreen activity on Curcuma rhizome extract and nanoparticles extract and making cream preparations. Extraction using the maceration methods with 96% ethanol solvent, concentrated with a rotary evaporator and the thick extract of Curcuma rhizome was made into nanoparticles by ionic gelation methods. Spray drying methods dried the nanosuspension of Curcuma rhizome extract. The nanoparticles formed were evaluated for particle size, zeta potential and particle morphology. The dry powder nanoparticles and extract of Curcuma rhizome were tested for antioxidant activity by DPPH (2,2-diphenyl-1-picrylhydrazyl) methods and sunscreen using a UV-Vis spectrophotometer at λ = 290-340 nm. The antioxidant activity showed the IC50 value of the Curcuma rhizome extract was 78.30 μg/mL and nanoextract was 116.51 μg/mL. The sunscreen testing result showed that the SPF (Sun Protective Factor) value of Curcuma rhizome extract at a concentration of 0,012% was 14.14 and nanoextracts at a concentration of 0.04% was 7.73. Curcuma rhizome extract has relatively strong antioxidant activity, while the nanoextract was moderate. The sunscreen activity of Curcuma rhizome extract and nanoextract has maximum protection and extra protection.